2015
DOI: 10.3109/02699052.2015.1018325
|View full text |Cite
|
Sign up to set email alerts
|

Widespread microglial activation in patients deceased from traumatic brain injury

Abstract: The findings indicate that TBI induces a widespread activation of brain microglia which affects all cortical areas, including those distant from the contusion site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Clinical evidence supports the idea that microglial and macrophage activation occurs rapidly following TBI. In autopsy of patients who have died following severe TBI, activated microglial morphologies were detected 2-10 days after injury (Velazquez et al 2015). In addition, increased cerebrospinal fluid levels of ferritin and soluble CD163, markers of macrophage and microglial activation, were elevated in pediatric patients within 3 days of severe TBI (Newell et al 2015).…”
Section: Classic Examples Of Neuroinflammation In the Context Of Centmentioning
confidence: 99%
“…Clinical evidence supports the idea that microglial and macrophage activation occurs rapidly following TBI. In autopsy of patients who have died following severe TBI, activated microglial morphologies were detected 2-10 days after injury (Velazquez et al 2015). In addition, increased cerebrospinal fluid levels of ferritin and soluble CD163, markers of macrophage and microglial activation, were elevated in pediatric patients within 3 days of severe TBI (Newell et al 2015).…”
Section: Classic Examples Of Neuroinflammation In the Context Of Centmentioning
confidence: 99%
“…In the same model, immune cells from the periphery were also recruited to the site of injury prior to neurodegeneration and MHCII expression was found at later time points in the striatum, as the inclusion pathology spread across the synapse from dopaminergic neurons in the SNpc to medium spiny neurons of the striatum [50]. Similarly, following a TBI in humans, activated microglia expand throughout the injured brain regions [114,155]. In mice following a single controlled cortical impact, activated microglia and macrophages continue to express elevated levels of MHCII and CD68, a year after the injury [90].…”
Section: Inflammationmentioning
confidence: 99%
“…Studies have also demonstrated neuroinflammation in various brain regions within the human population following TBI [119][120][121][122] . Molecular imaging studies have demonstrated microglial activation in populations of TBI patients as visualized via positron emission tomography using ligands for the mitochondrial translocator protein, TSPO, following brain injury [114,[119][120][121] .…”
Section: Neuroinflammation In Tbimentioning
confidence: 99%